2006
DOI: 10.1016/j.euroneuro.2005.11.004
|View full text |Cite
|
Sign up to set email alerts
|

AgRP(83–132) and SHU9119 differently affect activity-based anorexia

Abstract: Activity-based anorexia (ABA) mimics starvation and hyperactivity of anorexia nervosa patients in rats. Activation of the melanocortin (MC) system leads to hypophagia and increased energy expenditure in ad libitum fed rats. Therefore, activation of the MC system might underlie the development and propagation of ABA. Pro-opiomelanocortin (POMC) gene expression is normally decreased during negative energy balance. Strikingly, we found a transient up-regulation of POMC mRNA levels in the arcuate nucleus during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 65 publications
1
35
0
Order By: Relevance
“…24 Furthermore, increased body temperature has been reported in some treatments that increase survival in ABA, such as olanzapine 35 and the Agouti-related protein, AgRP, an endogenous antagonist of the MC system. 16,17 Interestingly, leptin also prevented hypothermia in rats but its additional food intake suppression aggravated weight loss and survival was impossible. 15 Because of the integrated, nonlinear nature of energy homeostasis neurocircuitry, the most up-todate efforts to find a single peptide or hormone for ABA recovery have been fruitless.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…24 Furthermore, increased body temperature has been reported in some treatments that increase survival in ABA, such as olanzapine 35 and the Agouti-related protein, AgRP, an endogenous antagonist of the MC system. 16,17 Interestingly, leptin also prevented hypothermia in rats but its additional food intake suppression aggravated weight loss and survival was impossible. 15 Because of the integrated, nonlinear nature of energy homeostasis neurocircuitry, the most up-todate efforts to find a single peptide or hormone for ABA recovery have been fruitless.…”
Section: Resultsmentioning
confidence: 97%
“…12,13 This animal model has advanced our understanding of the interaction between starvation and hyperactivity, and some pharmacological interventions have been moderately successful in partially preventing the development of the ABA outcome. These studies have focused on well characterized neuroendocrine systems involved in energy homeostasis, either on peripheral signaling to the hypothalamus, as in the case of the hormone leptin secreted by adipocytes, 14,15 or on central systems such as the melanocortin (MC), 16,17 and serotoninergic (5-HT) [18][19][20] systems. However, research using the ABA model has yet to identify a pharmacological agent that will aid rats to recover once running escalates and weight loss exceeds 20% of baseline body weight.…”
Section: Introductionmentioning
confidence: 99%
“…raISH procedure has been described previously (Hillebrand et al, 2006). Expression of AgRP, NPY, and POMC in the arcuate nucleus and expression of MCH and prepro-orexin in the LH were quantified using Image J software (National Institutes of Health, Bethesda, MD).…”
Section: Methodsmentioning
confidence: 99%
“…Another study of the same group likewise revealed no significant effect of centrally infused AgRP on running wheel activity. 107 Nevertheless, it has been suggested that a hyperactive melanocortinergic system underlies the SIH phenotype. 104,105,107 Other possible effectors downstream of the leptin receptor that might be implicated in SIH are the serotonergic and/or dopaminergic system as well as the hypothalamic-pituitary adrenal axis.…”
Section: Hyperactivitymentioning
confidence: 99%